(untitled) (Eurasian Journal of Philology Science and Education, 2026)
This article examines the linguistic behavior of Kazakh-speaking youth on the social media platform Threads from psycholinguistic and pragmatic perspectives. The main aim of the study is to identify the linguistic means used to express emotions, evaluations, and communicative intentions in online discourse. The research material consists of 94 publicly available comments posted by users aged 20 to 35, of which 10 content- and structurally representative comments were selected for in-depth qualitative analysis. The psycholinguistic approach focuses on manifestations of inner speech, emotional expressiveness, and cognitive mechanisms, while the pragmatic analysis explores communicative strategies, audience orientation, and the purposes of the messages. In addition, the study considers authorial stance, evaluative units, and the functions of discourse markers in the comments. The findings reveal the frequent use of non-standard (non-literary) vocabulary, code-switching, graphic markers, emojis, and punctuation-based cues that convey intonation. These features demonstrate a direct reflection of internal thinking processes, social positioning, and emotional states in linguistic expression. The study contributes to a deeper understanding of youth communication in digital environments and expands the theoretical framework of psycholinguistic and pragmatic research. The results may also be useful for educators, linguists, and psychologists studying online discourse and youth language practices. The findings make it possible to interpret the system of expressive resources in online discourse in relation to age-related factors, platform-specific communication constraints, and audience expectations. The conclusions may provide a basis for pragmatic modelling of Kazakh-language social media content and for describing processes of norm formation and language change in digital discourse. Keywords: psycholinguistics, linguistic behavior, online discourse, youth language, emotional expression.